O direito ao desenvolvimento sustentável: os royalties de petróleo de Coari-Amazonas - Viana , Rejane da Silva (2006)
The present work intended to demonstrate, that ahead of the extraordinary growth in prescriptions of royalties or financial compensations as a result of the exploration and production of oil and natural gas, a new scene begins to appear in the city of Coari in the State of Amazonas supporting the importance of these resources in its prescription confides. The work left of the Constitucional Law to the development and the perspectives for the Amazônia with the prospection of oil in the Basin of the Solimões. The main point of analysis will be to verify how these benefits are being used by the municipal administrations, the results of the investments, that already can be perceived. The adopted methodology was bibliographical consultation with survey and the analysis of social and financial facts of the city of Coari, adding information of the cities near by and using the pointers of human development and quality of life. Between the main results, it was gotten confirmation that royalties and special participations are important in the composition to the local governments offering the necessary resource for many investments, not being possible to determine its accurate use, or if verifying concrete actions for the promotion of a project of sustentabilidade and diversification of the local productive base. The use of royalties of form directed for the improvement in the quality of life of its habitants, justifies for the potential risk of ambient damages inherent to the activity of oil production and as form of indemnity for the exploration of resources you did not renew in order to prevent the economic decline being legitimate that such resources are used to make possible the potentialities of the region Words key: Amazônia; Sustainable development; Enviromental law; Royalties; Petrobras.